MINIMIZING THE SOCIAL DILEMMA: TAIWAN’S UNEXPECTED ACHIEVEMENT IN FIGHTING THE COVID-19 PANDEMIC - Huang, Kuochih (Investigación Económica, 2021)
Countries around the world find themselves trapped in a social dilemma amid the COVID-19 pandemic when most mitigation policies require sacrificing individuals’ interests for collective wellbeing. By examining Taiwan’s policy responses, this paper finds that while the cooperation for collective action does play a role, the main ingredient for its unexpected success is minimizing the grand-scale social dilemma, rather than fighting it head-to-head, through a set of carefully-designed measures. This paper further argues that Taiwan’s strategies are made possible by three underlying conditions that help to solve a series of collective action problems: The institutionalization and capacity building before the pandemic, the social coordination since the outbreak, and the political pressure from China. MINIMIZANDO EL DILEMA SOCIAL: EL INESPERADO ÉXITO DE TAIWÁN EN LA LUCHA CONTRA LA PANDEMIA COVID-19 RESUMEN El mundo se encuentra atrapado en un dilema social dentro de la pandemia COVID-19 cuando la mayoría de las políticas de migración requieren el sacrificio de los intereses individuales para el bienestar colectivo. Mediante el examen de las respuestas de política de Taiwán, en este artículo argumentamos que mientras la cooperación para la acción colectiva desempeña un papel, el principal ingrediente del éxito inesperado de este país es la minimización del dilema social de gran escala, más que la lucha directa contra la pandemia, a través de un conjunto de medidas diseñadas de forma cuidadosa. Argumentamos, además, que las estrategias de Taiwán son posibles debido a tres condiciones subyacentes que contribuyen a resolver una serie de problemas de acción colectiva: la institucionalización y la construcción de capacidades ante la pandemia, la coordinación social desde la irrupción de ésta y la presión política de China.